Violencias, razzias y collerats en espacios fronterizos. Los ataques e incursiones en tierras valencianas, huerta de Xàtiva, en el siglo XV (1427-1428). - CAÑIZARES GÓMEZ, MARÍA JOSÉ; SOLER MILLA, JUAN LEONARDO (Scripta)
The study analyses the cross-border relations between Valencia, Granada and Castilla after approaching the idiosyncrasy of border spaces between Iberian Christian and Muslim societies in the Iberian peninsula. Case study based on a specific episode: the attack on farmlands in Xativa at the end of 1427 and its consequences. We use a process estabilished with the objective of pursue "crim de collera" and socio-border instability.